Regulation of extravillous trophoblast invasion by uterine natural killer cells is dependent on gestational age - Lash, Gendie E; Otun, Harry A; Innes, Barbara A; Percival, Kathryn; Searle, Roger F; Robson, Stephen C; Bulmer, Judith N (Human reproduction (Oxford), 2010)
Extravillous trophoblast (EVT) cell invasion of uterine decidua and the inner third of myometrium is critical for successful pregnancy. Many decidual factors are likely to play a role in regulating this process. We have previously shown that cytokines, known to be produced by uterine natural killer (uNK) cells, such as TNF-alpha, TGF-beta1 and IFN-gamma inhibit EVT invasion. We therefore hypothesized that supernatants from purified uNK cells would inhibit EVT invasion. Total unfractionated decidual cell supernatants from 8 to 10 weeks gestation increased EVT invasion from placental villous explants, although uNK cell supernatants from 8 to 10 weeks gestation had no effect. In contrast, both total decidual and uNK cell supernatants from 12 to 14 weeks gestation stimulated EVT invasion. MMP-2, uPA, PAI-1 and PAI-2 levels did not differ under any of the conditions tested, whereas MMP-9 levels were increased in the presence of both total decidual and uNK cell supernatants from both gestational age groups. There was a decrease in the level of EVT apoptosis in the presence of uNK cell supernatant from 12 to 14 weeks, but not 8-10 weeks, gestation. Decidual uNK cell supernatants from 12 to 14 weeks gestational age stimulated EVT invasion, potentially by increasing MMP9 levels and reducing apoptosis. Total decidual cell isolates stimulated EVT invasion at both gestational ages investigated, potentially reflecting the complex nature of these cell culture supernatants.